Hepatocyte-specific knockout of HIF-2α cannot alleviate carbon tetrachloride-induced liver fibrosis in mice - Ye,Jianfang; Chen,Jie; Li,Yun; Sun,Liao; Lu,Hongyun (PeerJ, 2023)
Background The effects of hypoxia inducible factor-2α (HIF-2α) deficiency on liver fibrosis have not been demonstrated in a fibrosis model induced by carbon tetrachloride (CCl4). We aimed to examine whether hepatocyte-specific HIF-2α deletion could ameliorate CCl4-induced liver fibrosis in mice. Methods Hepatocyte-specific HIF-2α knockout mice were created using an albumin promoter-driven Cre recombinase. HIF-2α knockout (KO) mice and floxed control wild-type (WT) mice were fed a normal diet (ND) and received either twice weekly intraperitoneal injections of CCl4 solution (CCl4 dissolved in olive oil) or the corresponding amount of olive oil for 8 weeks. The indicators of liver function, glucose and lipid metabolism, and liver histology were compared among the different groups. Results Hepatocyte-specific HIF-2α knockout had no effect on the growth, liver function, glucose or lipid metabolism in mice. CCl4-treated KO and WT mice had a similar pattern of injury and inflammatory cell infiltration in the liver. Quantification of Masson staining, α-smooth muscle actin (α-SMA) immunohistochemistry, and the hydroxyproline (HYP) content revealed similar liver fibrosis levels between KO and WT mice injected intraperitoneally with CCl4. Immunohistochemistry analysis suggested that HIF-2α was mainly expressed in the portal area and hepatic sinusoids but not in hepatocytes. Bioinformatics analyses further indicated that HIF-2α expression was neither liver specific nor hepatocyte specific, and the effect of HIF-2α in hepatocytes on liver fibrosis may not be as important as that in liver sinuses. Conclusions Hepatocyte HIF-2α expression may not be a key factor in the initiation of liver fibrogenesis, and hepatocyte-specific deletion of HIF-2α may not be the ideal therapeutic strategy for liver fibrosis.
Keywords: HIF-2α; Liver fibrosis; Liver injury; Lipid metabolism